Breast feeding practices among rural women in a selected area of Bangladesh - Rahman, Mumtaz; Begum, Nasreen; Rahman, Md Mahbubar; Nayan, Shafia Khatun; Zinia, Sumsun Nahar (Northern International Medical College Journal, 2015)
Background : It has been already established that appropriate breast feeding practices reduce child morbidity and mortality; improve immunity in children besides being essential for their optimal growth and development. Objective : To evaluate the status of breast feeding practices among the women in a selected rural area of Bangladesh. Methodology : Descriptive, cross-sectional study was conducted between January to June 2013. A total 191 women, age between 18- 45yrs who had children below 2 years were selected purposively from a village. Mothers were the respondents and data were collected by face to face interview using pretested questionnaire. Results : Socio demographic characteristics of respondents revealed 80.63% were house wife; their mean age was 23.91yrs. Most of them were educated. Economical status was lower middle class. Exclusive breast feeding was found among 70.68% respondents and 75.92% mothers fed colostrums to their babies. During antenatal care 84.47% respondents got advice on breast feeding. Within one hour after birth 56.54% mothers initiated breast feeding. Total 24.08% mothers gave pre-lacteal feed. During childs sickness 92.67% respondents continued breast feeding. Conclusion : Exclusive Breast feeding practice among rural women which was higher than the national target. Educated mothers were more motivated and also those who received advices on breast feeding during antenatal care. Strengthening of Breast feeding counseling during antenatal care is recommended to maintain sustainability. Northern International Medical College Journal Vol.5(2) 2014: 345-348